Dahonggou Creek virus, a divergent lineage of hantavirus harbored by the long-tailed mole (Scaptonyx fusicaudus). Issue 1 (December 2016) - Kang, Hae Ji; Gu, Se Hun; Cook, Joseph; Yanagihara, Richard
Abstract Novel hantaviruses, recently detected in moles (order Eulipotyphla, family Talpidae) from Europe, Asia, and North America would predict a broader host range and wider ecological diversity. Employing RT-PCR, archival frozen tissues from the Chinese shrew mole (Uropsilus soricipes ), broad-footed mole (Scapanus latimanus ), coast mole (Scapanus orarius ), Townsend's mole (Scapanus townsendii ), and long-tailed mole (Scaptonyx fusicaudus ) were analyzed for hantavirus RNA. Following multiple attempts, a previously unrecognized hantavirus, designated Dahonggou Creek virus (DHCV), was detected in a long-tailed mole, captured in Shimian County, Sichuan Province, People's Republic of China, in August 1989. Analyses of a 1058-nucleotide region of the RNA-dependent RNA polymerase-encoding L segment indicated that DHCV was genetically distinct from other rodent-, shrew-, mole-, and bat-borne hantaviruses. Phylogenetic trees, using maximum likelihood and Bayesian methods, showed that DHCV represented a divergent lineage comprising crocidurine and myosoricine shrew-borne hantaviruses. Although efforts to obtain the S- and M-genomic segments failed, the L-segment sequence analysis, reported here, expands the genetic database of non-rodent-borne hantaviruses. Also, by further mining natural history collections of archival specimens, the genetic diversity of hantaviruses will elucidate their evolutionary origins.